2008
DOI: 10.1111/j.1745-4514.2008.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

ENZYMATIC CHARACTERISTICS OF ALCOHOL ACETYLTRANSFERASE FROMHANSENIASPORA VALBYENSIS, A NON-SACCHAROMYCESYEAST

Abstract: Alcohol acetyltransferase (AAT) catalyzing 2‐phenylethyl alcohol and acetyl co‐enzyme A (acetyl‐CoA) to form phenylethyl acetate in Hanseniaspora valbyensis was studied. The enzyme was solubilized from lipid particles using 1% Triton X‐100 and then purified by three steps of chromatographic separations with diethylaminoethlyl (DEAE) Sepharose, Sephadex G‐75 and Octyl Sepharose, respectively. Its molecular weight was estimated to be about 37 kDa. It was discovered that AAT was most active at pH 7.0 and 30C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Studies have shown that esters are synthesised by the lipase/esterase pathway ( Wang et al, 2008 ), alcohol transferase pathway ( Wolter et al, 1966 ) and alcohol dehydrogenase pathway ( Kusano et al, 1998 ). The lipase/esterase synthesis pathway, namely, the esterification reaction pathway, is the most common pathway used to generate esters in liquor ( Papamichael, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that esters are synthesised by the lipase/esterase pathway ( Wang et al, 2008 ), alcohol transferase pathway ( Wolter et al, 1966 ) and alcohol dehydrogenase pathway ( Kusano et al, 1998 ). The lipase/esterase synthesis pathway, namely, the esterification reaction pathway, is the most common pathway used to generate esters in liquor ( Papamichael, 2013 ).…”
Section: Introductionmentioning
confidence: 99%